How to deal with children’s violence? Implementation of child protection policies in Bekasi Regency, Indonesia - Aos Kuswandi; Ainur Rofieq; Siti Nuraini; Noer Kholis (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
According to data from the Ministry of Women Empowerment and Child Protection, the region of West Java has witnessed 819 cases of child violence. The West Java Province records indicate that Bekasi Regency has the highest incidence of child violence cases. The purpose of this study was to investigate the implementation of Law No. 35 of 2014, which amended Law No. 23 of 2002 on Child Protection, in the region of Bekasi Regency. This study used the qualitative research method with six variable of policy implementation are examined; 1) resources, 2) policy measures and standards 3) implementing agents' traits, 4) implementers' attitudes and tendencies, 5) interorganizational communication, and 6) social, economic, and political circumstances. The research outcomes indicate that the legislative policy has been effectively executed with respect to its scale and policy benchmarks, the attributes of the implementing actors, the disposition and inclination of the implementers, and inter-organizational communication. The enhancement of child protection in Bekasi Regency necessitates improvements in resource allocation, as well as the social, economic, and political circumstances.